Effect of Jin's Three-Needle Therapy Combined with Standing Digital OT Training on Upper Extremity Motor Function of Patients with Hemiplegia after Stroke - CHEN Xuanfang; WANG Chengling; ZHENG Huanchi; FU Wenkang; MAI Yunyi; WANG Junhua (康复学报)
ObjectiveTo observe the effect of Jin's three-needle therapy combined with standing digital OT training on upper extremity motor function of patients with hemiplegia after stroke.MethodsA total of 60 patients with upper extremity hemiplegia after stroke in the inpatient department of acupuncture-moxibustion and rehabilitation of Guangdong Second Traditional Chinese Medicine Hospital from January to June 2021 were divided randomly into control group and observation group, with 30 cases in each group. Both groups received routine medication and routine rehabilitation training. The control group received Jin's three-needle therapy on the basis of routine medication and routine rehabilitation training, and the three-needle points were selected at the contralateral temporal, the affected shoulder and hand [Quchi (LI11), Waiguan (TE6), Hegu (LI04)], Baihui (DU20) and Shuigou (DU26) acupoints. The even reinforcing-reducing method was conducted, and when the patients brought about the desired sensation, the needle was retained for 30 minutes, once a day, six times a week, lasting for eight weeks. The observation group received stan-ding digital OT training on the basis of the control group, 20 minutes a time, once a day, six times a week, lasting for eight weeks. Before treatment and eight weeks after treatment, Fugl-Meyer assessment-upper extremity (FMA-UE) was used to evaluate upper extremity motor function; Wolf motor function test (WMFT) was used to quantify the upper extremity motor ability; modified Barthel index (MBI) was used to assess the ability of activities of daily living.ResultsCompared with that before treatment, the FMA-UE, WMFT and MBI scores of both groups increased significantly after treatment (P<0.05). Compared with the control group, the FMA-UE, WMFT and MBI scores of the observation group increased significantly after treatment, and the difference was statistically significant (P<0.05).ConclusionJin's three-needle therapy combined with standing digital OT training can effectively improve the motor function of upper extremity and the ability of activities of daily living of patients after stroke.